2018
DOI: 10.1101/385096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signals of variation in human mutation rate at multiple levels of sequence context

Abstract: Our understanding of mutation rate helps us build evolutionary models and make sense of genetic variation. Recent work indicates that the frequencies of specific mutation types have been elevated in Europe, and that many more, subtler signatures of global polymorphism variation may yet remain unidentified. Here, we present an analysis of the 1,000 Genomes Project (phase 3), suggesting additional putative signatures of mutation rate variation across populations and the extent to which they are shaped by local s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Another signature, *AC → *CC, has been observed at higher frequency in East Asians compared to Africans in the 1kGP and the SGDP (Aikens et al, 2019;Harris and Pritchard, 2017). These two studies also found heterogeneous frequency of this signature among 1kGP Japanese individuals.…”
Section: Mutational Signaturesmentioning
confidence: 59%
See 2 more Smart Citations
“…Another signature, *AC → *CC, has been observed at higher frequency in East Asians compared to Africans in the 1kGP and the SGDP (Aikens et al, 2019;Harris and Pritchard, 2017). These two studies also found heterogeneous frequency of this signature among 1kGP Japanese individuals.…”
Section: Mutational Signaturesmentioning
confidence: 59%
“…Strong population enrichments of a mutational signature suggests important genetic or environmental differences in the history of each population (Harris, 2015;Harris and Pritchard, 2017). Harris and Pritchard further identified distinct mutational spectra across a range of populations, which were further examined in a recent publication by Aikens et al (Harris and Pritchard, 2017;Aikens et al, 2019).…”
Section: Mutational Signaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct sequence data from plants and insect also reveal a mutagenic effect of heterozygosity (32). Finally, different three-base combinations show markedly different mutation probabilities in different human populations (34,35) an observation that has been extended more generally to sequence context (36). That the types of mutations differ so strongly between human populations lends credence to the idea that the overall rate might also vary.…”
Section: Introductionmentioning
confidence: 84%
“… Aggarwala and Voight (2016) proposed a statistical model that takes parameters from observed frequency of mutations within 5-mer or 7-mer, while Zhu et al (2017) introduced a log-linear model for mutation frequency analysis that also considers up to 5-mers. It has also been found that variability of mutation in human genome between different populations of human genome are dependent on context beyond the immediate flanking bases ( Aikens et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%